Under three flags - Neill, Stephen (Friendship Press, 1954)
Memoirs of a former civil servant and minister in Bangladesh, on political conditions in Bangladesh under the British, Pakistani, and Bangladeshi administrations; chiefly covers the period, 1933-1981.